Financial institutions, financial fragility and crises - Büyükkarabacak, Berrak (My University, 2004)
In this thesis the relationship between financial liberalization, financial fragility and crises is analyzed. More specifically, it focuses on the impact of financial liberalization on financial fragility in Turkey's context and tries to understand the effects of financial liberalization in Turkey esp. in three markets; stock markets, banking system and exchange rate system, and second, to explain the link between these markets fragility and financial crises. To do so, the data is used for the period 1970-2003 for Turkey, since Turkey is the one of the developing countries, which is a fast financial liberalizer and experienced severe financial crises during the past three decades. Towards this end, a model including exchange rates, current account and capital account balances is estimated. In order to account for differences induced by the degree of financial liberalization, two dummy variables are used. The first one stands for the partially liberalized system (1980-88), the second one is for the fully liberalized period (1989-2002). Results suggest that financial liberalization had adverse impacts on growth in both of the periods. Furthermore, fully liberalized system increases the probability of having a financial crisis in Turkey. From these results it can be concluded that liberalization process must be gradual esp. in emerging countries. Otherwise fragile markets can cause severe financial crises.

Bu tezde finansal liberalizasyon, finansal kırılganlık ve finansal krizler arasındaki ilişki incelenmiştir. Finansal liberalizasyonun Türkiye ekonomisinde yaşanan finansal kırılıganlık üzerindeki etkisi araştirilmistir. Özellikle üc piyasa üstünde durulmuştur: bankacılık sistemi, menkul kıymetler borsasi ve döviz piyasaları. Bu ilişki tesbit edildikten sonra yaşanan kırılganlık ve finansal kriz olasılıgı arasinda ki ilişkiye bakilmiştir. Veri olarak 1970-2002 yılları icin önemli makro ekonomik indikatörler kullanilmistir. Türkiye dünyadaki gelişmekte olan ülkeler arasındadir ve 1980 sonrasinda hızlı bir liberalizasyon sürecine girmistir. Ancak, son 15 yılda yaşanan ciddi finansal krizler finansal liberalizasyonun sonuclarını mercek altına almistir. Yaşanan rejim değisikliği kullanılan kukla degişkenlerle analiz edilmiştir. Taban dönem 1970-1980 dönemi olarak belirlenmiş, ilk kukla degişkeni 1980-1988 yılları icin kısmi liberalizasyonu temsil etmektedir. İkinci kukla değişkeni 1989-2002 yılları için tam liberalizasyon dönemi için kullanılmıştır. Sonuçlar her iki liberalizasyon döneminde de büyümenin taban yıllarina göre negatif etkilendiği yönündedir. Bunun yanı sıra tamamen libarelleşmiş dönemde Türkiye ekonomisinde kriz yaşanma olasılıgı artmıstır. Bu sonuçlardan yola çıkarak varılabilecek sonuç Türkiye ve Türkiye gibi gelişmekte olan ülkeler liberalizasyon sürecine hizli ve hazirliksiz girmemelidirler. Geçiş süreci daha dengeli olmalidir. Ancak böylelikle sermaye hareketlerinin yarattigi kirilganlikla baş edilebilir.
Keywords: Ekonomi; Finansal Kriz